Dubovyi K. V. Mistakes and losses in voice-over movie translation - Dubovyi K. V. (Philological Treatises, 2020)
The article deals with difficulties of voice-over translation due to which there appear mistakes and losses. Frequent losses of word play, metaphors, songs deprive the movie of its inherent imagery. The mistakes may be caused by: lack of attention on the side of the translator, editor or dubbing actors; absence of the final editing stage on which the text of the translation is compared to the video; wrong choice of translation equivalent or using inappropriate transformations; problems and losses in translating culturally-biased and equivalent-lacking units as explanations and comments cannot be included into the script translation. The translator of the movie should realize that his/ her work is creative as is very similar to literary translation.